Characterization, quantification and management of China's municipal solid waste in spatiotemporal distributions: A review. (March 2017) - Gu, Binxian; Jiang, Suqin; Wang, Haikun; Wang, Zibo; Jia, Renfu; Yang, Jie; He, Sheng; Cheng, Rong
Highlights: A multi-year generation inventory of municipal solid waste (MSW) was reviewed in China. Uncertainty analysis of MSW's physical components was estimated. Recommendations for MSW's management were proposed. Abstract: Municipal Solid Waste (MSW) is a heterogeneous waste stream, which is harmful for human health and the ecological environment if it is not well managed. Based on results from different authors by analyzing the generation, physical components and management of MSW from different cities, this paper presents an overview of the temporal trends and spatial variation characterization of MSW generation and its physical components in China. Total MSW generation has increased from 31, 320 thousand tons in 1980 to 178, 602 thousand tons in 2014, and MSW generation per capita has also increased from 448.3 g to 653.2 g. The distribution of MSW generation is mostly concentrated in the coastal southeastern region, as well as large point sources of more than 200 thousand tons per year are mostly distributed in Jiangsu, Zhejiang, Shandong, Hebei and Guangdong provinces. The review shows that the largest proportion of food waste, plastics and paper is 61.2% (54.2–65.9%, 95% CI), 9.8% (7.2–14.0%, 95% CI), 9.6% (6.7–12.3%, 95% CI), respectively, in 2014; the best estimates of other waste were as follows: 3.1% textile, 2.1% glass, 1.1% metal, 1.8% wood and grass, 1.3% rubber and leather, 1.8% ceramic, 2.5% ash, 1.2% hazardous waste, and 4.5% miscellaneous. To better manage China's MSW, several possible and appropriate solutions (e.g., concentrating on key regions, intensifying source separation, promoting green lifestyle, and establishing specialized regulations and policies) should be adopted, which might facilitate the application of China's 13th Five, and identify gaps in our knowledge of MSW management subject.